A study of two Chinese-style Clarinet Works Colors from China and Hommage to China from the Perspective of Cultural Holism - Congjie Zhao (Qubahan Academic Journal)
Cultural Holism is a guiding ideology for music study proposed by Chinese scholar LUO Yifeng in 2006. It was proposed mainly based on the background of increasingly frequent cultural exchanges in the world today, and contemporary Western classical music works illustrate this trend by increasingly incorporating non-Western music elements. Cultural Holism accordingly aims to interpret the application and integration of different musical elements in the related works from a more comprehensive and neutral perspective. This study selects two representative works - Colors from China and Hommage to China - from a series of recent Chinese-style clarinet works created by Italian composers Michele Mangani and Giuseppe Ricotta, and conducts detailed musical analysis of the two works from the perspective of Cultural Holism in order to present specific examples of innovative uses and combinations of Western and Chinese musical elements, thereby bringing about a clearer and deeper understanding of these works.